PENGARUH PENDEKATAN METAKOGNITIF DAN KEMAMPUAN AWAL MATEMATIS TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS SISWA - Fadhila Putri; Abdul Muin; Khairunnisa Khairunnisa (ALGORITMA: Journal of Mathematics Education, 2019)
The purpose of this research is to analize the influence of metacognitive approach and Student’s MPK to Students’ Mathematical Reflective Thinking Skills. The research was conducted in one of SMP in South Tangerang. The method used in this research is quasi experiment with two group randomized subject posttest only-design, which involve 55 students as sample. In this research students were categorized by their mathematical skills before given the treatment test. The indicator of students mathematical reflective thinking skills that was measured in this research are (a) describing a situation or mathematical problem, (b) identifiying a situation or mathematical problem, (c) interpretating, (d) evaluating, (e) predicting, (f) making a conclusion. The results of the study are: (1) metacognitive approach which is applied by the researcher causes the improvement of students mathematical reflective thinking ability. (2) the interaction beetween learning approach and Student’s Mathematical Prior Knowledge has effect to students mathematical reflective thinking ability, (3) there is different average of students mathematical reflective thinking between high and low group of Student’s MPK when the metacognitive and conventional class is joined, (4) there is no influence of Student’s MPK to students mathematical reflective thinking in class which using metacognitive approach or conventional approach. The conclusion is metacognitive approach can be used to improve mathematical reflective thinking ability of students at high and low group of Student’s MPK. In other side conventional learning is suitable to improve mathematical reflective thinking ability at students ofmedium Student’s MPK.